Modified method of cervical conization with hybrid use of a cold knife and an electric knife for high-grade squamous intraepithelial lesions - Weifeng Zhang; Yi Lin (Journal of International Medical Research, 2022)
Objective To evaluate the feasibility and surgical outcome of the modified method of cervical conization with hybrid use of a cold knife and an electric knife. Methods A retrospective analysis of cervical conization for high-grade squamous intraepithelial lesions was performed between January 2020 and December 2020. Traditional cold knife conization and modified conization were used. The clinical characteristics and surgical outcomes were compared between these methods. Results Ninety-two patients with high-grade squamous intraepithelial lesions were included. Traditional conization was performed in 46 patients, and the modified method was used in 46 patients. There were no differences in clinical characteristics, such as age, menopausal status, and conization height, between the methods. Intraoperative blood loss with the modified method was significantly lower than that with traditional conization (27.6 ± 4.7 vs 51.3 ± 18.3 mL). Postoperative vaginal bleeding requiring emergent measures, such as prolonged gauze compression, sutures, or electrocautery, was significantly less with the modified method than with traditional conization (4.3% vs 17.4%). A median follow-up of 10.2 months showed no significant difference in persistence or recurrence between the methods. Conclusions The modified method of cervical conization with hybrid use of cold and electric knives may be a good alternative to traditional cold knife conization.